Pengaturan Fungsi Pemerintah Kabupaten dalam Menyelenggarakan Urusan Administrasi Kependudukan dan Implementasinya di Kabupaten Kupang - Wiwin Maryani Mada; Saryono Yohanes; Rafael Rape Tupen (Lembaga Pengembangan Kinerja Dosen, 2024)
As an organizing element, the government is obliged to carry out population administration affairs which is an important aspect of government governance which aims to ensure accurate and valid identifiation for every resident. With the enactment of law number 24 of 2013 concerning amendments to law number 23 of 2006 concerning population administration, it aims to improve and perfect regulations related to populations administration, with a focus on improving services to the community. The formulation of the problem in this research is: (1) How is the function of the district government regulated in carrying out population administration affairs? (2) To what extent is the implementation of the district governments function in carrying out population administration affairs in Kupang district ? The research used in this writing is normative juridical research and is supported by empirical juridical research. The results of this research show : (1) how the functions of the district government are regulated in carrying out population administration, standard operating procedures, and ownership of population documents. (2) to what extent is the implementation of the district governments function in carrying out population administration affairs in Kupang district, which includes : service system, form of service and factors that become obstacles : inadequate facilities and infrastructure, low human resource, and still minimal budget.